Actuarial approach in a mixed fractional Brownian motion with jumps environment for pricing currency option - Shokrollahi, Foad; Kilicman, Adem (SpringerOpen, 2015)
This research aims to investigate the strategy of fair insurance premium actuarial approach for pricing currency option, when the value of foreign currency option follows the mixed fractional Brownian motion with jumps and the European call and put currency option are presented. It has certain reference significance to avoiding foreign exchange risk